Pengaruh Diversitas Dewan Komisaris dan Dewan Direksi Terhadap Kinerja Perusahaan (Studi Empiris: Perusahaan Manufaktur Di BEI Periode 2014-2018) - LILIS GUSTIANA; Yeasy Darmayanti; Meihendri Meihendri (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2021)
This study aims to determine the effect of board of commissioners and board of directors diversity on company performance in manufacturing companies listed on the Indonesia Stock Excharge for the 2014-2018 period. By using purposive sampling method, obtained 45 samples of manufacturing companies listed on the Indonesia Stock Exchange. Based on the results of hypothesis testing, it was found that the age diversity of the board of commissioners had no significant effect on company performance; the diversity of board of commissioners educational background had no significant effect on company performance, the diversity of board of commissioners tenure had a significant effect on company performance. While the diversity of board of directors age had a significant effect on company performance, diversity the of educational backgrounds of the board of directors does not have a significant effect on company performance, and the diversity of tenure of the board of directors does not have a significant effect on company performance. Keywords : Company Performance, Age, Education, Tenure, Board Of Commissioners Board Of Directors.